2017
DOI: 10.1186/s12912-017-0247-x
|View full text |Cite
|
Sign up to set email alerts
|

How school nurses experience and understand everyday pain among adolescents

Abstract: BackgroundPain problems are a rapidly growing health problem found among both children and adolescent, and about 15–30% have reported chronic pain problems. School nurses in Norway meet adolescents with various ailments, including pain. Yet research on how school nurses perceive the pain experienced by adolescents is limited. The aim of the present study was to explore how school nurses explain and experience the everyday pain of adolescents.MethodA qualitative study with an explorative design comprising five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 39 publications
2
35
0
Order By: Relevance
“…It is also a vulnerable period in life, and can be challenging with respect to independence from caregivers, increase of autonomy and social role transitions [ 5 , 6 , 8 11 ]. Although the vast majority of Norwegian adolescents are content with their lives and generally report good health [ 16 ], an increasing number of adolescents in Norway and other countries report psychosocial problems and health complaints in everyday life such as loneliness, stress, insufficient and poor-quality sleep, pain and high intake of over-the-counter analgesics (OTC analgesics) [ 9 , 11 20 ], indicating a need for continued efforts in health promotion among adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…It is also a vulnerable period in life, and can be challenging with respect to independence from caregivers, increase of autonomy and social role transitions [ 5 , 6 , 8 11 ]. Although the vast majority of Norwegian adolescents are content with their lives and generally report good health [ 16 ], an increasing number of adolescents in Norway and other countries report psychosocial problems and health complaints in everyday life such as loneliness, stress, insufficient and poor-quality sleep, pain and high intake of over-the-counter analgesics (OTC analgesics) [ 9 , 11 20 ], indicating a need for continued efforts in health promotion among adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Recordings were transcribed verbatim for analysis. A phenomenological hermeneutic approach to content analysis was selected 4. The methods employed as well as the approach to data analysis were appropriate for the topic,5 and demonstrate a rigorous approach to qualitative research taken on by the study team.…”
Section: Methodsmentioning
confidence: 99%
“…As a daily point of healthcare contact for school children, school nurses are responsible for addressing pain in school children so they may fully engage in school activities. The study by Høie and colleagues4 leverages the experiences and opinions of junior high school nurses to determine how these nurses address pain in adolescent school children.…”
Section: Contextmentioning
confidence: 99%
“…According to McCaffery's [45] definition, pain is "whatever the experiencing person says it is, existing whenever he says it does," and it could seem as if this understanding does not reflect nonclinical pain. The issue of not being believed could mirror the perception that today's young people may be regarded as less sturdy than previous generations [46,47]. Research has revealed the increasing pressure on today's adolescents with greater stress physically, socially, and emotionally [48].…”
Section: Juggling Pain With Everyday Lifementioning
confidence: 99%
“…Studies also show that more girls than boys report pain; moreover, living with pain affects girls more negatively than boys. Further, pain problems can negatively influence a young person's quality of life and health [4,9,10]. Experiencing pain in adolescence is related to pain problems later in adulthood, and research indicates that pain problems might also have serious long-term consequences [11][12][13].…”
mentioning
confidence: 99%